L’esperienza estetica di fronte all’animale: una sua possibile definizione in prospettiva ontologico-esistenziale - Pasqualin, Chiara (Scenari, 2024)
In contemporary discussion, especially in the fields of aesthetics of nature and evolutionary animal aesthetics, the question about the meaning and definition of a supposed aesthetic appreciation of animals has been posed. In contrast, classical theorists of animal ethics have omitted to consider the role and significance of the aesthetic disposition and approach to animals. The present paper intends to explore this topic from an ontological-existential perspective based on the texts of Martin Heidegger and Karl Jaspers. We will outline a broad and non-anthropocentric definition of aesthetic experience that is applicable not only to a special class of objects, i.e. the works of art, but also to animals. We will show, in particular, that an authentic aesthetic experience of animals is characterized by four essential features: disinterestedness, the occurrence of an existential shock, a metaphysical aspect and an ethically binding character.